ANALISIS PELAYANAN KESEHATAN BAGI PASIEN BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) DI PUSKESMAS PABUARAN TUMPENG KOTA TANGERANG - Jumrotani, Jumrotani; Mulyono , Doddy (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study aims to evaluate the quality of healthcare services provided to BPJS patients at Puskesmas Pabuaran Tumpeng, Tangerang City. The research uses a quantitative approach, with data presented in numerical form and analyzed using statistical techniques. The total number of respondents consisted of 100 BPJS patients. Meanwhile, a total of 12 Puskesmas staff were selected through accidental sampling, comprising 2 doctors, 8 nurses, and 2 administrative staff. The assessment of service quality refers to the SERVQUAL model developed by Zeithaml and Parasuraman, as cited in Harbani Pasolong (2013:9), which includes six dimensions: reliability, assurance, tangibles, empathy, responsiveness, and equity. The results indicate that overall service quality is categorized as good. The reliability dimension reflects adequate medical services, especially in diagnosis and medication, although long queues and delays in doctors’ attendance remain common complaints. The assurance dimension is rated well due to the competence of medical personnel, though the communication regarding patients’ rights is still lacking. In terms of tangibles, facilities are fairly clean and well-maintained, but limitations in supporting infrastructure such as waiting chairs and medical equipment are noticeable, particularly during peak patient visits. The empathy dimension shows friendly service from most staff, though inconsistencies in attitude are observed, especially towards elderly patients and low-income groups. The responsiveness dimension falls into the fair category, as administrative processes are slow and urgent complaints are not handled optimally. Finally, the equity dimension is assessed positively, although there is still a public perception that certain patients receive preferential treatment. In conclusion, the majority of respondents rated the healthcare services at Puskesmas Pabuaran Tumpeng as good, with an overall satisfaction rate of 73%. These findings indicate that despite some shortcomings, the healthcare services provided have generally met acceptable standards.